Understanding the podocyte immune responses in proteinuric kidney diseases: from pathogenesis to therapy - Jiang, Hong; Shen, Zhirang; Zhuang, Jing; Lu, Chen; Qu, Yue; Xu, Chengren; Yang, Shufen; Tian, Xuefei (Frontiers in Immunology, 2024)
The glomerular filtration barrier, comprising the inner layer of capillary fenestrated endothelial cells, outermost podocytes, and the glomerular basement membrane between them, plays a pivotal role in kidney function. Podocytes, terminally differentiated epithelial cells, are challenging to regenerate once injured. They are essential for maintaining the integrity of the glomerular filtration barrier. Damage to podocytes, resulting from intrinsic or extrinsic factors, leads to proteinuria in the early stages and eventually progresses to chronic kidney disease (CKD). Immune-mediated podocyte injury is a primary pathogenic mechanism in proteinuric glomerular diseases, including minimal change disease, focal segmental glomerulosclerosis, membranous nephropathy, and lupus nephritis with podocyte involvement. An extensive body of evidence indicates that podocytes not only contribute significantly to the maintenance of the glomerular filtration barrier and serve as targets of immune responses but also exhibit immune cell-like characteristics, participating in both innate and adaptive immunity. They play a pivotal role in mediating glomerular injury and represent potential therapeutic targets for CKD. This review aims to systematically elucidate the mechanisms of podocyte immune injury in various podocyte lesions and provide an overview of recent advances in podocyte immunotherapy. It offers valuable insights for a deeper understanding of the role of podocytes in proteinuric glomerular diseases, and the identification of new therapeutic targets, and has significant implications for the future clinical diagnosis and treatment of podocyte-related disorders.